If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -3ln(x) = 11 Multiply ln * x 1 + -3lnx = 11 Solving 1 + -3lnx = 11 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3lnx = 11 + -1 Combine like terms: 1 + -1 = 0 0 + -3lnx = 11 + -1 -3lnx = 11 + -1 Combine like terms: 11 + -1 = 10 -3lnx = 10 Divide each side by '-3nx'. l = -3.333333333n-1x-1 Simplifying l = -3.333333333n-1x-1
| 2x+2+5x-10=180 | | 500=80-10x | | 10(x-3)-7=8x+1 | | y=-4.99+0.079x | | x+14=x+14 | | 5x^2=18x-9 | | f(x)=2x^4+8x^3-7 | | (10x^2-5x)+(-4x+2)= | | 3/4*5/13 | | xy+2y+2x+4= | | x(4x-5x)=9 | | 2i+(x+yi)=6whatisx+yi | | 2x+6x+10=90 | | x+15=7.6 | | 8(4+y)+4y=3 | | 78/42 | | 8(x-4)-3=6x+1 | | -6(x+2)-16=19+7 | | 7k+19=5 | | 8x-2=6x+5 | | m=6n+8 | | x+x-.66=30 | | X^2-2/3=30 | | 9x^2-5x-1= | | 91=6(12+b) | | 25-x÷2=x/3 | | 5/42x=-6/42 | | 2b-3b= | | 5/42=-6/42 | | 9x-5=7x+29 | | -5(3x-4)= | | 25c^2+20ct+4t^2=0 |